Rancang Bangun Bot-Server & Client Telegram dengan Python Untuk Otomatisasi Pendaftaran Kampus dengan Layanan Informasi dan Sistem Pembayaran Terintegrasi pada STKIP Amal Bakti - Siregar, Fakhran Arifin; Puspita, Khairani (Jurnal Teknologi Informasi Indonesia (JTII), 2025)
The rapid development of information technology has influenced the efficiency of academic administration in universities. However, many higher education institutions still use manual systems in new student registration, information services, and payment processes. This study aims to design and implement an automation system using a Telegram bot built with Python to assist in registration, provide academic information, and integrate payment services at STKIP Amal Bakti. The system was developed using the Waterfall methodology, which includes analysis, design, implementation, and testing phases. The results of testing indicate that the Telegram bot effectively streamlines registration, improves data accuracy, and enhances the efficiency of academic services. This research contributes to digital transformation in higher education institutions and demonstrates the potential of automation using chatbots in administrative services.